THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE TEAMS GAMES TOURNAMENT (TGT) ON LEARNING OUTCOMES ON THE MATERIAL OF RATIONALIZING THE DENOMINATOR OF ROOT FORM - Nabila Nurhaliza; Ratna Yestina; Agis Mulyani; Supratman . (JME (Journal of Mathematics Education), 2023)
Team Games Tournament (TGT) learning is well prepared with the right procedures, it will be better than conventional methods such as lectures that tend to be monotonous. This encourages researchers to conduct research with the title "The Effectiveness of the Team Games Tournament (TGT) Learning Model on Mathematics Learning Outcomes on the Material of Rationalizing Denominators of Root Forms". This study aims to analyze the effect of mathematics learning outcomes of class X IPA 1 MAN 1 Tasikmalaya City on the material of rationalizing the denominator of the root form presented with the Teams Games Tournament (TGT) learning model. The type of research used is quantitative with action research. Data collection techniques are done by observation and giving instruments in the form of pre-test and pot-test questions and minute papers. The sample was taken with purposive sampling technique so that 15 students were obtained as research subjects. Before conducting hypothesis testing, data requirements were first tested including: normality testing using SPSS 25 with the Shapiro Wilk Test and homogeneity testing using SPSS 25 with the Shapiro Wilk Test. Hypothesis testing using the t-test. The results of this study indicate that student learning outcomes in the material rationalize the denominator of the root form by using the Teams Games Tourbament (TGT) learning model there is a difference between the pre-test and post-test results.